1966
DOI: 10.1104/pp.41.8.1293
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic Electron Transport Chain of Chlamydomonas reinhardi. III. Light-Induced Absorbance Changes in Chloroplast Fragments of the Wild Type and Mutant Strains

Abstract: Sum;inary. Light-induced absorbance changes were investigated in chloroplast fragments of wild type Chlamiiydomitonas reinhardi and 5 different mutant strains having impaired photosynthesis. Two absorbance changes were detected, 1 hftving a maximtum at 553 nm and the other at 559 nm. The component exhibiting the 553 nm change is a cytochrome similar to cytochrome f from higher plant chloroplasts. The component exhibiting the 559 nm change has the properties of a cytochrome similar to cytochrome b,. Two of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
44
0

Year Published

1967
1967
1977
1977

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(45 citation statements)
references
References 9 publications
1
44
0
Order By: Relevance
“…is redutced by ascorbate, and supposed to be located in a non-cy-clic pathway in the place Levine and Gormani (16) have shown that a spectrumn of light-induced oxidation of chloroplast fragments from Chlam"Ydomionas reinhardi has a max,inmum at 560 nm wlhich might be attributed to the cy.tochrome b559 found bv others. However, they failed to see light-induced oxidation of b563 in their preparation, in which this component had probably been completely oxidized during sonication (cf.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…is redutced by ascorbate, and supposed to be located in a non-cy-clic pathway in the place Levine and Gormani (16) have shown that a spectrumn of light-induced oxidation of chloroplast fragments from Chlam"Ydomionas reinhardi has a max,inmum at 560 nm wlhich might be attributed to the cy.tochrome b559 found bv others. However, they failed to see light-induced oxidation of b563 in their preparation, in which this component had probably been completely oxidized during sonication (cf.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of 2 types of cvtochrome b, cvtochrome b563 or be, and cvtochrome b559, in photosyntlhetic ellectron transfer svstemls has been pointed otit in spinach chloroplasts (2,5,1) and in Chlamnydomtolnas reinhardi (15,16,24). Cytochrome b563 may be auto-oxidizable (13), is not reduced by ascorbate, and has recentlv been considered to be a member of a cyclic pathway around photosystem I in spinach chloroplasts (5, l) atnd Chlainydonmonas (9,15).…”
Section: Discussionmentioning
confidence: 99%
“…The unicellular green algae Chlarnydowiionas recinliardi and Scenedesmnius obliqutus have been used in this way (1)(2)(3)6 For NADP-a the reaction mixture (2.0 ml) contained chloroplast fragments (20-25 ug chlorophyll) and the following in umoles: potassium phosphate buffer, pH 7.0, 20; KCI, 40; MgCl2, 5; ferredoxin purified from wildtype C. rcinhardi, 0.0005; and NADP, 0.5. For NADP-b the reaction mixture contained, in addition to the above, the followitng in Anmoles: DPIP, 0.1; sodium ascorbate, 10; and DCM1IU, 0.02.…”
mentioning
confidence: 99%
“…A technique is described for detecting mutants of Chlaryvdoiimoias rciniar'di that lhave impaired photosynthesis. It is based on the fact that when photosynthetic electron transport is blocked there may be an increase in the level of fluorescence similar to that obtained in the presence of an inhibitor of photosynthetic electron transport such as dichloropohenyldimethylurea.One way to obtain information about the mechanism of photosynthesis is to study mutant organisms that are unable to carry out normal photosynthesis.The unicellular green algae Chlarnydowiionas recinliardi and Scenedesmnius obliqutus have been used in this way (1)(2)(3)6 …”
mentioning
confidence: 99%
See 1 more Smart Citation